2008
DOI: 10.1128/iai.01609-07
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role for Iron Regulation in Coxiella burnetii Pathogenesis

Abstract: In gram-negative bacteria, iron acquisition proteins are commonly regulated by Fur (ferric uptake regulator), which binds iron-regulated promoters (the Fur box). We hypothesized that Coxiella burnetii requires iron and employs an iron-regulatory system and used various approaches to define a Fur regulon. Cloned C. burnetii fur complemented an Escherichia coli fur deletion mutant. A ferrous iron transporter gene (CBU1766), a putative iron binding protein-encoding gene (CBU0970), and a cation efflux pump gene (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…It has been reported that the global transcription profiles of the hyperthermophilic archaeon Thermococcus kodakarensis, a close relative of P. furiosus, were similar under iron-sufficient and iron-limited conditions, suggesting a lessthan-stringent response to iron availability (14). Similar nonresponsive transcriptional effects of iron were also observed with the obligately anaerobic and mesophilic bacteria Coxiella burnetii and Dichelobacter nodosus (15,16).…”
Section: T He Hyperthermophilic Anaerobic Archaeon Pyrococcus Furiosussupporting
confidence: 53%
See 2 more Smart Citations
“…It has been reported that the global transcription profiles of the hyperthermophilic archaeon Thermococcus kodakarensis, a close relative of P. furiosus, were similar under iron-sufficient and iron-limited conditions, suggesting a lessthan-stringent response to iron availability (14). Similar nonresponsive transcriptional effects of iron were also observed with the obligately anaerobic and mesophilic bacteria Coxiella burnetii and Dichelobacter nodosus (15,16).…”
Section: T He Hyperthermophilic Anaerobic Archaeon Pyrococcus Furiosussupporting
confidence: 53%
“…Similar results have been reported for several other anaerobes. The pathogenic bacterium Coxiella burnetii lacks annotated iron acquisition and storage systems, and its Fur regulon consists of three genes (the iron transporter gene feoB, a gene encoding a putative cation efflux protein, and a gene predicted to encode an iron-binding protein) (15), indicating that iron-dependent transcriptional regulation plays a minor role in iron metabolism. In Dichelobacter nodosus, the Fur regulon includes genes encoding two putative iron transporters (YfeA and CbiK) and a manganese superoxide dismutase (SodA) (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepcidins (Hamp1 and Hamp2) reduce iron availability for invading microorganisms by reducing extracellular iron concentrations [35]. As has been recently suggested, greater iron availability in males may favor C. burnetii replication [36]. It has also been shown that hepcidins are differentially expressed in male and female mice [37], [38].…”
Section: Resultsmentioning
confidence: 98%
“…The bacterium also possesses thiamine pyrophosphate and flavin mononucleotide riboswitches, which can regulate gene expression by sensing the levels of their cognate molecules [95]. Although iron is not believed to play an important role in virulence, a Fur-based regulatory system that detects and responds to iron concentrations is also present [96]. It has also been shown that Coxiella modulates the autophagic pathway in host cells, probably to compensate for a lack of nutrients within the PV [97].…”
Section: How Coxiella Regulates Its Genesmentioning
confidence: 99%